Image Classification of Temperature Distribution Using Fourier Series Strategy - Salim, M.A.; M. Rosdzimin, A. R.; Osman, K.; Noordin, A.; Mohd Rosli, M.A. (Journal of Mechanical Engineering and Technology (JMET), 2015)
Abstract *